Animal tooth pendants from Spiginas and Donkalnis as instigators of a discussion on technological traditions, intergroup exchange and mobility in the early and middle Holocene in Central and northeastern Europe - Osipowicz, Grzegorz; Piličiauskienė, Giedrė; Piličiauskas, Gytis; Orłowska, Justyna (Journal of archaeological science, reports, 2024)
•Technology of animal pendants was used to study the mobility of Stone Age hunters.•We analysed traceologically 16 collections of animal pendants from Mid and NE Europe.•Pendants from Mesolithic burials at Spiginas and Donkalnis were studied in detail.•Three major technological traditions were distinguished in early and middle Holocene.•Technological studies were coordinated with stable isotope ratio measurements. This article attempts to verify the possibility of studying the mobility patterns of prehistoric communities based on the technological features of the artefacts, identified through traceological analyses. The research subject were animal tooth pendants from several dozen key early and middle Holocene hunter-gatherer-fishers sites in Central and Northeastern Europe. The starting point for the studies was traceological research conducted on a collection of pendants from Mesolithic burials at Spiginas (grave 4) and Donkalnis (graves 2, 4, and 5) in Lithuania. These results were compared with the findings, as yet largely unpublished, from microscopic tests conducted by the authors on 12 collections of artefacts from major early and middle Holocene sites in Poland, Lithuania, Latvia, and Estonia together with literature information about collections from other sites, in these areas and from sites in Russia, Sweden, Denmark and Germany, and were used to examine ways in which cord attachment areas were prepared in animal tooth pendants in Central and Northeastern Europe. In this regard, three major technological traditions were distinguished in the region which allows analysis of intercultural influences and the flow of people in the early and middle Holocene. An important part of this study involved co-ordinating the results of the technological analyses of the pendants from Spiginas and Donkalnis with the findings of stable isotope ratio measurements (87Sr/86Sr) conducted on the human remains from these cemeteries. Both research tools have been shown to be complementary in the context of research related to the mobility of early Holocene groups.